Making Activator Materials Active Carbon From Wedi Skin Salak (Salacca edulis Reinw) With ZnCl2 Activator as Adsorbent to Reduce Fenol Content - Ardianti, Aprillia Dwi; Anshori, Mohammad (Science Education and Application Journal, 2024)
Making Activator Materials Active Carbon From Wedi  Skin Salak (Salacca edulis Reinw) With  ZnCl2 Activator as Adsorbent to Reduce Fenol Content.  Wedi salak skin in Bojonegoro as an activated carbon material can provide an alternative for activated carbon manufacturing materials by utilizing environmentally friendly natural materials. The wedi salak skin is modified by treatment in the sun, in the roast, and in the oven in the manufacture of activated carbon which is then activated with ZnCl2 and then tested the adsorbs power of this salak skin activated carbon against phenol reduction. The adsorbent material that reduces the concentration of phenol the most is the roasted adsorbent material with a final phenol concentration of 2.15 mg/L so that the concentration of phenol absorbed is 297.85 mg/L at a mass of 1.5 g. The results of the analysis show that each variation of the activated carbon variation can reduce the concentration of phenol. The results obtained from this study are the type of activated carbon material whose highest absorption efficiency is the type of activated carbon material roasted at 99.28% with a mass of activated carbon of 1.5 g. Based on the results of the analysis, it can be seen that each variation of the type of activated carbon material will experience a decrease in concentration as the mass of the adsorbent increases. The greater the mass of the adsorbent, the adsorption ability will also increase. Each type of activated carbon material also experienced an increase in percent removal along with an increase in adsorbent mass. The results of research on the effect of activated carbon mass, also show that the adsorption capacity value decreases with increasing adsorbent mass. In this research data, the largest capacitance value was 112.87 mg/g at the smallest mass of 0.5g. The decrease in adsorption capacity is caused by the active side of the adsorbent that has not all bonded with the adsorbate.